Complements to the Theoretical Treatments of the Electron Collision with : An R-Matrix Approach - V. Stancalie (Journal of Spectroscopy)
This paper presents new refined results from the theoretical treatment of electron collision with the Fe-peak element Co3+. We have investigated the relevance of relativistic effects on the accurate representation of the target electron wave functions within the Breit-Pauli R-matrix approach. The calculated values for fine-structure levels are compared with the available experimental data in Atomic Structure Database of the National Institute for Standards and Technology. The agreement between the calculated and the experimental data is reasonably good, the energy difference average percentage of the low-lying levels usually agreeing to within 3.6% of each other. For completeness, we summarize herein the existing theoretical R-matrix treatments intended specifically to explore the role of including configuration interaction wave functions both in the target-state expansion, and in the ()-electron quadratically integrable function expansion. To the best of our knowledge, the work reported herein describes for the first time a detailed calculation for this atomic system, and the results are relevant to the laboratory and astrophysical plasmas.